The international training and research program on groundwater governance in Asia: Theory and practice - Sharma, Bharat R.; Villholth, Karen G.; Mukherji, Aditi (CGIAR Challenge Program on Water and Food, 2009)
CGIAR-CPWF Project “International Training and Research Program on Groundwater Governance in Asia: Theory and Practice” was designed and implemented by International Water Management Institute (IWMI) to address the deficiencies in human capacity of managing groundwater in the two large basins of the world- the Indus-Gangetic basin and the Yellow River basin. The basic premise of the project was that proper groundwater management needs to be built on informed knowledge of professionals from the region, with emphasis on inter-disciplinary knowledge and understanding of the actual groundwater situation in the rural areas. This objective was achieved through development of an international courseware on the subject and actual enhancement of the capacity of existing institutions and about 80 professionals working at junior and senior levels and engaged in media dissemination in the basin states involved in groundwater research and management so that they could undertake more integrated, multi-disciplinary and sustainable approaches to groundwater governance.